Towards a Prospective Communication Model for University-Industry Collaborations in Uganda - Kayondo, Barbara N; Kamondo, Moses Tuhame (University of Dar es Salaam Library Journal, 2024)
University-industry collaborations (UICs), which are frequently aided by the government, are thought to be essential to enhancing local and national innovation systems. Previous studies have identified barriers to UICs, but there is a dearth of empirical knowledge about the types of UICs and their challenges in the context of developing prospective models to enhance UICs, thereby restricting our ability to execute UICs. This study seeks to determine a prospective communication model for UICs by examining the various forms of UICs and the communication models used by universities and industries for collaboration. The study also establishes the challenges in UICs and measures to address them. The study adopted a qualitative research approach focusing on the service industry with three (03) service firms that have collaborated with the University of Kisubi, and one academic institution which is the University of Kisubi. The study findings reveal that the various forms of UIC in Uganda include student projects in the form of internships, research projects, and funding of research projects. The study findings also reveal that the barriers to UICs which include lack of trust, fear of knowledge link, and incompatibility occur at different stages. The study concludes that a communication model for UIC is pertinent to solving the barriers to UICs and enables the execution of UICs. The current study also provides a guiding framework for both university and industry practitioners by developing a consolidated communication model for UICs. Theoretically, by integrating the Theory of Communicative Action into UICs, our study provides a robust theoretical foundation for understanding the dynamics of communication in these partnerships and proposes models to enhance collaborations. Universities and industries ought to generate relevant collaboration partners and establish personal links using the communication model. Keywords: University-industry Collaboration, communication model, collaboration barriers https://dx.doi.org/10.4314/udslj.v19i2.6